120 Public education funding and firearm mortality in the United States. (5th May 2020) - Orji, Whitney; Meanley, Steven; Hatchimonji, Justin; Dolan, Abby
Abstract : Purpose: We sought to assess the association between public education funding and county-level firearm mortality in the United States. Approach: Spatial analyses were conducted to assess the associations between a 5-year aggregated (2013–2017) county-level firearm mortality rate and public education funding. Public education funding was calculated by school district-level per-pupil spending and adjusted by the Cost Wage Index to account for geographic variation in wages and costs.1, 2 Funding data from 2003 and 2010 were used to account for a lag effect and to evaluate effects of the nadir in state-level funding after the Great Recession.3–5 Spatial autocorrelation, hotspot, and geographically weighted regression analyses were performed. Results: Geographic hot spots were primarily identified in central, rural counties of the U.S. In the regression model, education funding from 2003 exhibited a small effect size (b=0.08, se=0.03, p=0.002) on firearm mortality. Statistically-significant covariates included county-level proportions of Black residents (b=0.04, se=0.02, p=0.038), residents <18 years old (b=0.06, se=0.02, p=0.012), and residents living in urban areas (b=-0.05, se=0.02, p=0.013). 2010 data yielded similar trends. Conclusions: Unexpectedly, higher school funding was associated with higher firearm mortality. Given the broad nature of per-pupil rate measures for education funding, future studies should explore the extent (e.g. proportion) and in what capacities (e.g., programming) funding streams are allocated specifically to address gun violence as well as community and individual-level risk factors. Significance: School-related factors like truancy and poor school performance are linked to gun violence victimization among youth6, 7, implicating schools as a critical platform to address individual and structural causes and consequences of the gun violence epidemic in the U.S.8, 9 The extent to which adequate public education funding informs firearm mortality remains poorly understood.